Enhanced Recovery After Surgery (ERAS)Protocols Evidence-based Strategies to Improve Postoperative Outcomes Across Surgical Specialties - Mehmood, Yasir; Syed, Yashal; Tauseef , Muhammad Abdullah; Adeel-Ur-Rehman; Ahmed, Faraz; Malik, Hussain (Indus Journal of Bioscience Research, 2025)
The study included 240 patients who received elective General or Ear, Nose and Throat surgeries, to determine how well ERAS was followed and the post-surgical outcomes. It aimed to find out if ERAS improves both the recovery and satisfaction of patients. It was found through descriptive statistics that the patients’ average age was 46.3 and the participants included very similar numbers of men and women. Most patients had positive experiences with their perioperative care, according to the new data. A logistic analysis was run to discover why postoperative complications might tie to the level of ERAS applied. Those with low or moderate scores on the post-surgery survey were more likely to develop complications compared to those who fully obeyed ERAS. For this reason, using all features of ERAS reduced risks following surgery and increased safety after the operation. In addition, a one-way ANOVA was done to discover if patient satisfaction varies based on how exactly ERAS is followed. Evidence showed that closely following ERAS is linked to improved patient satisfaction, indicating that both outcomes for patients and their satisfaction improve when these rules are used. The findings show that using ERAS protocols regularly in surgery today is essential. Additionally, the research encourages better training for medical staff, continuous supervision of ERAS adherence and recommends using these approaches in other medical institutions to support better surgery, fewer complications and improved patient care.